Effects of Fulvic Acid on Growth and Nitrogen Utilization Efficiency in M9T337 Seedlings - Yu, Bo; Wang, Laiping; Cui, Dongdong; Gao, Wensheng; Xue, Xiaomin; Nie, Peixian (Plants (Basel), 2023)
Both fulvic acid (FA) and nitrogen (N) play important roles in agricultural production in China. Plants typically show a higher nitrogen utilization efficiency (NUE) under FA application. However, the role of FA application in apple growth and NUE remains unclear. A hydroponic culture experiment was performed, and M9T337 seedlings (a dwarf apple rootstock) were used as the experimental subjects. The biomass, photosynthesis, accumulation, and distribution of photosynthates, N absorption and assimilation, and relative gene expression in the seedlings were examined after treatment with five different concentrations of FA (0, 60, 120, 180, and 240 mg·L−1, represented by CK, FA1, FA2, FA3, FA4, respectively). The results showed that the seedling dry weight and 15NUE were enhanced by FA, and both were highest under the FA2 (the concentration of fulvic acid is 120 mg·L−1) treatment. Further analysis revealed that under the FA2 treatment, the root morphology was optimized, and the root activity was relatively high. Compared with CK (control, the concentration of fulvic acid is 0 mg·L−1), the FA2 treatment strengthened photosynthesis, elevated the key enzyme activities related to C metabolism, upregulated the gene expression of sugar transport proteins, and increased the root sorbitol and sucrose contents, which suggested that the FA2 treatment optimally affected the root growth and N absorption because it enhanced photosynthate synthesis and the leaf-to-root translocation of photoassimilates. The seedlings in the FA2 treatment group also showed a significantly higher NO3− influx rate and NRT (nitrate transporter) gene expression in the roots. Moreover, relatively high N metabolism-related enzyme activities in the leaves and roots were also observed under the FA2 treatment. The isotope labeling results showed that the optimal FA2 supply not only promoted seedling 15N absorption but also optimized the distribution of C and N in the seedlings. These results suggested that an optimal FA supply (120 mg·L−1) enhanced seedling NUE by strengthening photoassimilate synthesis and transport from leaves to roots, regulating N absorption, assimilation, and distribution.